2002
DOI: 10.1177/07419325020230040301
|View full text |Cite
|
Sign up to set email alerts
|

Education Reform, High-Stakes Assessment, and Students with Disabilities

Abstract: Over the past decade, the state of Virginia has been at the forefront of education reform efforts to implement new standards coupled with high-stakes assessments. The Virginia accountability system creates standards for individual students, schools, and school districts. Students with disabilities have been fully included in the Virginia education reform efforts. Participation by students with disabilities in the high-stakes assessment program has been relatively active, and these students have shown small but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…Over the years, assessments and graduation requirements have led to differentiated diploma options. Some states have used assessments to make decisions about student promotion or high school graduation (deFur, 2002). In a recent survey of 46 states and the District of Columbia, 27 state education agencies reported that they have or will have exit exams that require students to take a highstakes assessment to receive a diploma (Johnson & Thurlow, 2003).…”
Section: No Child Left Behindmentioning
confidence: 99%
“…Over the years, assessments and graduation requirements have led to differentiated diploma options. Some states have used assessments to make decisions about student promotion or high school graduation (deFur, 2002). In a recent survey of 46 states and the District of Columbia, 27 state education agencies reported that they have or will have exit exams that require students to take a highstakes assessment to receive a diploma (Johnson & Thurlow, 2003).…”
Section: No Child Left Behindmentioning
confidence: 99%
“…test and the consequences related to failing to receive a regular high school diploma, such as not being accepted into a college, trade school, or military program. Students with disabilities may conclude that they have little chance of passing the test and either fail to put forth any effort or drop out of school (Albrecht & Joles, 2003;deFur, 2002). It is evident from our findings that instruction in testtaking strategies can play some role in reducing students' anxiety about testing.…”
Section: Test Anxiety Inventorymentioning
confidence: 57%
“…According to Defur (2002), "the current system of standards does not acknowledge or value that there are multiple views of participating in, or contributing to, society or of demonstrating one's competence. Although such instruments may serve as a measure of a narrow band of important learning, they certainly cannot capture the breadth and depth of all learning that is important.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study of Virginia special education administrators revealed that many of these administrators reported increased referral rates, which they believed to be linked to the state's accountability system (Defur, 2002). According to Defur (2002), "an increasing number of general education teachers were voicing resentment at having students with disabilities in their classes and that collaborative efforts between special and general educators had decreased" (p. 208). This concern was also supported by the Virginia study.…”
Section: Avoiding Potential Problemsmentioning
confidence: 99%